Smart window for tuning transparency and noise absorption - Shrestha, Milan (Nanyang Technological University, 2019)
Sound and light are everywhere in a city. The unwanted noise of traffic and direct or reflected glares of the sun are annoyances to urban residents which adversely affects the urban livability. As parts of the high-rise-building facades, smart windows could mitigate the sound-and-light pollutions by replacing the conventional glass glazing and curtains. Existing solutions of smart windows are imperfect and costly for simultaneous control of light transmission and sound absorption. For example, an optical smart window based on polymer dispersed liquid crystals (PDLC) ages when exposed to UV for years; an electrochromic window is pricey and prone to leakage; micro-perforated glass absorbers are only effective to absorb mid-frequency sound over a moderate bandwidth. Their absorption spectrum is fixed and was not tunable to target spectrum variation of noise. Alternative technology of smart window is in need of tunable acoustic and optical properties. This work presented novel smart windows capable of regulating the light transmission and the sound absorption. Being useful for daylighting and privacy, the smart optical window can switch between transparent and opaque. In addition, they can be equipped with a transparent micro-perforated dielectric elastomer actuator (DEA) for tunable and broader sound absorption. These smart windows can be used to make green smart building and could potentially enhance the urban livability. While glass is the choice of material for making a window panel, the rigidity of glass prohibits its electro-mechanical activation to tune its optical and acoustic properties. Instead, soft dielectric elastomers are preferable as electroactive materials. Recently, dielectric elastomer actuators (DEA) with metallic or graphene electrodes were used to make tunable window devices. Their surface roughness is variable by means of surface microwrinkling or unfolding through dielectric elastomer actuation. As a tunable optical surface scatter, it turns transparent with a smooth surface like a flat glass; but it turns ‘opaque’ (translucent) with the micro-rough surface. However, nanometric metallic thin films are not clear enough while few-layer graphene electrodes cannot be frosted enough to switch between clear and translucent. In addition, they needed a large area strain to unfold the microwrinkles, covering only a small fraction of the window. These issues motivate the present development of tunable optical films based on microwrinkling of TiO2 and poly (3, 4-ethylene dioxythiophene)-poly styrene sulfonate (PEDOT-PSS) thin films on a dielectric elastomer. While using a low-strain induced microwrinkling and unfolding, these optical tunable devices exceed the performance of a PDLC based smart window device. Recently, a tunable acoustic membrane absorber has been developed based on a membrane DEA. Its resonant frequency is tunable by controlling membrane tension through voltage activation. While the peak absorption is high, the absorption bandwidth for this absorber is very narrow. To solve this problem, this work developed a micro-perforated dielectric elastomer actuator (MPDEA) absorber with tunable acoustic absorption spectrum. The elastomer membrane’s tension and holes diameter are changed using voltage activation; this, in turn, tunes its acoustic resonant frequency. In addition, PEDOT:PSS thin film electrodes were ink-jet printed on the elastomer substrate to make transparent MPDEA absorber, which promises to make large-area tunable absorber for windows.